مصطلح السفهاء في القرآن الكريم -دراسة موضوعية - مجور, شيماء; جرمان, رميساء (University of Eloued-جامعة الوادي, 2022)
"تعد هذه الدراسة خطوة على درب الدراسات القرآنية، وهي بعنوان مصطلح السفهاء في القرآن الكريم ـ دراسة موضوعية ـ . وتهدف هذه الدراسة إلى إخراج دراسة قرآنية نربط فيها الواقع بكتاب الله وبيان منهج القرآن الكريم في تناول موضوع السفهاء، واتبعنا إلى حل إشكالات عديدة تخص عنوان دراستنا من بينها: ما تعريف السفهاء ؟وكيف عبر القرآن الكريم عن السفهاء في سياقاته المختلفة؟ حيث قسمنا موضوع بحثنا إلى مبحث تمهيدي تضمن تعريف التفسير الموضوعي مع إبراز أهميته وبيان أنواعه، ثم ذكرنا دوافع اختيار هذا موضوع ، كما أدرجنا أهمية وأهداف الموضوع ثم الخطوات المنهجية وكذلك الدراسات السابقة . وأجبنا عن الإشكالية السابقة من خلال ثلاث مباحث: الأول: تناول الدراسة المصطلحية للسفهاء في القرآن الكريم وفيه أربعة مطالب تضمنت المعنى اللغوي والاصطلاحي للسفهاء وأهم التصريفات والاشتقاقات، واستخراج المعاني القريبة لها ثم الوجوه والنظائر . أما المبحث الثاني احتوى على أربعة مطالب تضمنت صفات السفهاء في الأمور الدنيوية وكذا الأمور الأخروية، ثم تطرقنا إلى الكشف عن حكم الحجر على السفيه وبعض الأحكام المتعلقة بتصرفاته . أما عن المبحث الأخير فقد جاء كمجموعة دلالات ومفاهيم شرعية مستنبطة من آيات صفات السفهاء في القرآن الكريم. وقد ختمنا هذا الموضوع بخاتمة سردنا فيها أهم النتائج المستخلصة عن السفهاء، ومما توصلنا إليه أن السفه مذموم لا بد من اجتنابه واجتناب مخالطة أصحاب الجهل والسفاهة، ولابد على كل مسلم أن يستحضر خوف الله ومحاسبة النفس. ""- This study is cosidered as a step on the Quranic studies ,under the title (the term of *Sufahaa* fools in the holy Quran ,and the aim of this study is to conclude with a Quranic study then we relate a reality with the holy book and the explanation of the approach of the noble Quran in dealing with the topics of fools *Sufahaa* ,we have solved many problems related to our study which are: definition of fools *Sufahaa* ?How the Quran express fools in different contexts ? - Our research is divided into introductory study that includes: definition of the objective exegesis with it is importance and it is types,then the reasons for choosing this topic which is Sufahaa fools also we dealt with the importance and the aim of the topic the Methodological steps,besides to the previous studies, we have answered our problem through three chapters: - Chptera One: tke up the terminolojical study of the Sufahaa fools in the Holy Quran with it is linguistics and idiomatic meaning in addition to the most important conjugation and derivation and take up the closest meaning to the term Sufahaa fools and it is synonyms and antonyms . - The second Chapter: dealt with the characteristics of Sufahaa in the worldly and hereafter matters, then the stone rule over them and other rules related to their actions .The third Chapter tackled Arguments from Holy Quran it is verses about the characteristics of Sufahaa-fools. - Finally we have concluded with the most important results about the fools, we have reached that this people are the worst ever and we have to avoid touching with the ignorant and the foolish people, and every muslim have to neglect and avoid this kind of people and to evoke the fear of Allah and self-judgement."
مذكرة ماستر
Keywords: سفهاء , سفاهة; foolishness, foolishness